CRIMINAL LAW POLICY IN BLASPHEMY ENFORCEMENT BASED ON RESTORATIVE JUSTICE - Natamiharja, Rudi; Siswanto, Heni; Banjarani, Desia Rakhma; Setiawan, Ikhsan (Jurnal Bina Mulia Hukum, 2023)
Policies for resolving religious blasphemy in Indonesia are regulated in Law Number 1/PNPS/1965 concerning the Prevention of Blasphemy of Religion and Article 156a of the Criminal Code. Sentences are often repressive and do not fulfill the value of justice. The formulation of the problem in this article is: what is the criminal law policy in the settlement of blasphemy and what kind of settlement model is chosen to handle the case. This research method is normative legal research with a statutory approach based on primary legal materials. The research results show that the imposition of punishment is the main solution. Meanwhile, the model chosen in the resolution of defamation of freedom of expression according to the concept of restorative justice uses an integrated approach that tries to implement penal and non-penal efforts simultaneously to fulfill justice for the perpetrators of defamation, including involving the role of the community through the Religious Communication Forum (FKUB). Suggestions that need to be conveyed are that criminal law policies are still being implemented, but harsh criminal sanctions are softened by using the concept of restorative justice, bearing in mind that not every case of blasphemy deserves a harsh sentence.